Psychotic symptoms and disorders and the risk of violent behaviour in the community - Swanson, Jeffrey (Criminal behaviour and mental health, 1996)
This study uses data from the Epidemiologic Catchment Area (ECA) surveys to examine the strength of the association between psychotic symptoms and violent behaviour, controlling for underlying mental disorder, substance abuse, sociodemographic characteristics and use of mental health services, in a representative sample of community residents. A replication is conducted of a study that found an increased risk of violence associated with a particular cluster of psychotic symptoms involving perceived threat and internal control-override (TCO). Respondents who reported TCO symptoms were about twice as likely to engage in assaultive behaviour as those with hallucinations or other psychotic symptoms, and about five times as likely as those with no mental disorder. The combination of substance use disorders with TCO symptoms added significantly to the risk of violent behaviour. Those with a history of using mental health services also posed a higher risk of violence, probably due to the differential selection of more severely ill and "dangerous" individuals into treatment settings. Copyright Ř 1996 Whurr Publishers Ltd